HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG DAMPAK MEROKOK BAGI KESEHATAN DENGAN MOTIVASI BERHENTI MEROKOK DI SEKOLAH MENENGAH PERTAMA SMPN 1 SINDANG JAYA - Nia P; Eka Noviana Nasriyanto; Lastri Mei Winarni (Nusantara Hasana Journal, 2022)
On percentage of first-time smokers aged 10 years in Banten Province is 25.91%, the prevalence of smoking in the population aged >10 years in Tangerang is 26.21%, smoking behavior in Banten Province is 18.749%, while the number of smoking habits in Banten is 18.749%, Tangerang City is 3,279% (Riskesdas, 2018). Smoking is proven to be a risk factor for diseases that can attack the human body and this disease is not contagious, for example coronary heart disease, stroke, cancer, chronic lung disease and diabetes mellitus which are the main causes of death in Indonesia. the world, including in Indonesia. Objective to determine the relationship between the level of knowledge about the impact of smoking on health with motivation to quit smoking at SMPN 1 Sindang Jaya. The design uses a cross sectional design technique, where the research was conducted at SMPN 1 Sindang Jaya with a total of 105 respondents on July 18, 2022. The data analysis in this study used univariate and bivariate analysis. Results showing a picture of adolescent knowledge half of the respondents have sufficient knowledge (53.3%), good (32.2%), less (11.4%). motivation to quit smoking most of the respondents have poor motivation (59.0%), good motivation (41.0%). The results of the bivariate analysis showed that there was a relationship between the level of knowledge about the impact of smoking on health and the motivation to quit smoking in junior high school SMPN 1 Sindang Jaya with p-value = 0.001 (p≤ = 0.05). Nurses are expected to be able to perform their role optimally to provide nursing care about health education and knowledge about the dangers of smoking to health.